Monitoring cow comfort and rumen health indices in a cubicle-housed herd with an automatic milking system: a repeated measures approach. Issue 1 (December 2015) - Vanhoudt, Arne; van Winden, Steven; Fishwick, John; Bell, Nicholas
Abstract Background Cow rumination and lying behaviour are potentially useful and interrelated indicators of cow health and welfare but there is conflicting evidence about how reliable these measures are. The objective of this study was to quantify the variation of indices of cow comfort and rumen health in a herd with an automatic milking system for which husbandry was relatively constant, in order to propose an alternative approach to optimising the use of these indices when continuous monitoring is not available. During a period of 28 days, standing index, cud chewing index and rumination index were observed. Results The daily mean standing index ranged between 9.0 and 18.0 per cent, cud chewing index between 43.5 and 74.0 per cent, and rumination index between 49.0 and 81.0 per cent. The point of lowest variation in the indices was determined as that with the lowest coefficient of variation. The coefficient of variation was lowest for data collected between 240 and 270 minutes after refreshing of the bedding material on the cubicles for both the standing index and rumination index, and for data collected between 120 and 150 minutes after refreshing of the bedding material on the cubicles for the cud chewing index. Conclusions In spite of relative constant husbandry practices in a herd with an automatic milking system, the variation in the standing index, cud chewing index and rumination index was still considerable. This suggests these measures should be repeated on several consecutive days, according to population size and wanted margin of error, to be representative and useful.